Analysis of the concession contract No. 001 of 10 January 2017, carried out between the ANI and the Concessionaire Accesos Norte de Bogotá S.A.S, under the scheme of Public Private Partnerships APP. (2020)
This document provides a general overview of the regulations governing the modality of recruitment under the APP scheme, taking as its guiding principle Law 1508 of 2012 and other regulations amending it; thereby understanding the form of application in project development according to the type of guidance that is most appropriate, APP with Public Initiative or APP with Private Initiative, which provide different edges that must be judiciously analyzed, always seeking to obtain the greatest benefit for the parties. Each initiative offers benefits depending on how they are analyzed, therefore, and in order to respond to the problem posed in this trial, three specific objectives were established, the first of these allowed the identification of the rules applicable to APP, which in turn generated a clearer understanding of its origin and of the need and importance of its application in the different infrastructure projects that originated in the country. The second objective was to describe the advantages obtained in this contract by applying the APP contracting modality, thus aiming at obtaining more tools for solving the problem. Without a doubt, the modality applied in this APP contract with private initiative, led to the obtaining of profits such as i) execution of the contract by a private concessionaire; formed by 5 Colombian companies specialized in different fronts, with recognition, experience, soundness, suitability, state-of-the-art technology and track record in the implementation of road infrastructure projects, (ii) involvement of the private sector in addressing public sector constraints, iii) implementation over time, facilitating the planning and planning of each stage of the project, avoiding excessive and unjustified failures and delays, (iv) failure to commit public resources and investing them in other projects of social interest; (v) Recovery of the capital invested by the private sector, through the administration and maintenance of the works carried out and others delivered. The last objective, aimed at explaining the levels of budget execution and progress, was gratifying to learn that the percentage of implementation is very close to the programmed percentage, demonstrating once again the effective control exercised by the parties over each of the stages defined in the project.